1998
DOI: 10.1093/tropej/44.6.362
|View full text |Cite
|
Sign up to set email alerts
|

Brief report. Study of plasma albumin, transferrin, and fibronectin in children with mild to moderate protein-energy malnutrition

Abstract: With the increasing awareness of incipient and subclinical malnutrition in children several nutritional indices have been suggested for the early recognition of protein-energy malnutrition (PEM). We evaluated plasma albumin, transferrin, and fibronectin levels in 15 children with PEM and compared them with those of 10 well-nourished children. The results demonstrated that plasma albumin is a poor indicator of mild to moderate PEM. On the other hand, plasma transferrin and fibronectin are sensitive indicators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Results for α-1-antitrysin were inconsistent [128]. So-called negative acute phase proteins like transferrin [94] [130], α-2-HS-glycoprotein [135], fibronectin [133] [138] and pre-albumin [122] [138][139] were consistently reduced in malnourished children, even without infections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results for α-1-antitrysin were inconsistent [128]. So-called negative acute phase proteins like transferrin [94] [130], α-2-HS-glycoprotein [135], fibronectin [133] [138] and pre-albumin [122] [138][139] were consistently reduced in malnourished children, even without infections.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study found lower CRP levels in malnourished than well-nourished children with similar infections, despite higher levels of IL-6 [129]. So-called negative APP were uniformly low in children with malnutrition and infection, including transferrin [94] [127] [130][133], α-2-HS-glycoprotein [134][136], pre-albumin [122], fibronectin [132], and α-2-macroglobulin[127].…”
Section: Resultsmentioning
confidence: 99%
“…Acutely malnourished children are generally deficient in multiple nutrients concurrently (19, 106), but the pattern and extent of deficiencies is extremely heterogeneous (both between individuals in the same setting, but especially between different settings and regions) and abnormalities in nutrient trafficking mean some body compartments may even experience nutrient excess. For example, despite whole-body iron deficiency, free iron may be high in plasma due to protein deficiency limiting production of the iron-transporter protein transferrin (124, 125) or actively sequestered in macrophages during infection to restrict iron availability for pathogens (22). Ideally, diets used for animal models of undernutrition should be based on either: (i) nutrient intake profiles of undernourished children in a defined setting, or (ii) levels of existing nutrients, ideally taking into account the circulating nutrient pool as well as any tissue stores.…”
Section: Improving Assessment Of Immune Function In Undernutritionmentioning
confidence: 99%
“…[7][8][9][10][11] Bu amaçla albümin, transferin, prealbümin (Transthyretin) ve fibronektin gibi serum proteinleri kullanılmaktadır. 4,8,13,15 Serum transferrin plazmada demiri taşıyan bir beta-globulindir. Transferrinin plazma düzeyleri beslenme etmenlerinden ve demir metabolizmasından etkilenir.…”
Section: Discussionunclassified